2021
DOI: 10.1017/cjn.2021.212
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Cognitive Spectrum of Artery of Percheron Infarction: 1-Year Follow-Up

Abstract: Objective: Survivors of patients with artery of Percheron infarction (API) often have a prolonged and disabling form of cognitive impairment that remains insufficiently characterized. We aimed to examine the clinical and cognitive features of API in the short and long term after stroke. Methods: We reviewed 6400 patients with a first-ever stroke included in the Stroke Registry between 2011 and 2021. The diagnosis of API was based on clinical diagnosis and imaging confirmation. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A 2014 study also found that, in 15 patients with AOP infarctions, mental status changes and oculomotor disturbances were the two most common findings [9]. These findings were corroborated in a separate stroke registry study that found 10 patients with AOP infarcts to have behavioral, cognitive, and consciousness disturbances at the onset of stroke [10]. However, studies report variations in symptoms in a spectrum of seven patterns as follows: mental status changes, aphasia, behavior/memory impairment, ocular movement abnormalities, cerebellar signs, motor deficits, and nonspecific signs, such as seizures, hyperthermia, and hypersomnia [8,11].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A 2014 study also found that, in 15 patients with AOP infarctions, mental status changes and oculomotor disturbances were the two most common findings [9]. These findings were corroborated in a separate stroke registry study that found 10 patients with AOP infarcts to have behavioral, cognitive, and consciousness disturbances at the onset of stroke [10]. However, studies report variations in symptoms in a spectrum of seven patterns as follows: mental status changes, aphasia, behavior/memory impairment, ocular movement abnormalities, cerebellar signs, motor deficits, and nonspecific signs, such as seizures, hyperthermia, and hypersomnia [8,11].…”
Section: Discussionmentioning
confidence: 85%
“…Further research is needed to clarify the true long-term prognosis of all four types of AOP infarctions. For patients with AOP infarctions that contain thalamic and midbrain involvement, there can be persistent long-term deficits in executive function and processing speed, as well as both working and executive memory one year after the infarction [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison with similar reports (table 2) shows that some degree of cognitive impairment is commonly observed after AoP strokes, particularly when no rehabilitation is performed or is delayed. Moreover, a systematic review on longitudinal trajectories of cognition after AoP stroke showed that 50% of the subjects had persistent and clinically relevant cognitive deficits after 1 year 28. In these patients, executive functions were the most affected initially, while episodic memory deficits were also observed 1 year later 28…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a systematic review on longitudinal trajectories of cognition after AoP stroke showed that 50% of the subjects had persistent and clinically relevant cognitive deficits after 1 year 28. In these patients, executive functions were the most affected initially, while episodic memory deficits were also observed 1 year later 28…”
Section: Discussionmentioning
confidence: 99%